Tuberculosis of the Knee: : A Rare Case Series - Budi, Ikhsan; Ningrum, Egi Novita; Rachma, Siti; Djasfar, Seftiwan Pratami; Jonesti, Wilfadri Putra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Tuberculosis (TB) can manifest as pulmonary or extrapulmonary TB, with the latter involving various organs and tissues outside the lungs. Knee TB, a form of skeletal TB, is a relatively rare condition, accounting for only 0.09% to 0.15% of all TB cases. Here, we present a case series diagnosed and managed at Undata Hospital, Central Sulawesi, highlighting the clinical presentation, diagnostic challenges, and treatment strategies for this uncommon condition. We present two case series involving male patients with knee pain, swelling, and limited range of motion, accompanied by systemic symptoms such as fever and weight loss. Both patients had previous pulmonary TB diagnoses and underwent radiological examinations, including chest X-ray and knee radiography. Microbiological analysis was performed using GeneXpert MTB/Rif, and histopathological examination confirmed TB in both cases. The first patient, diagnosed with clinical pulmonary TB and knee TB, responded well to anti-tubercular therapy (ATT) and surgery. The second patient, with ongoing pulmonary TB, was diagnosed with knee TB after surgery and biopsy. Both patients showed significant improvement in symptoms after treatment and surgery, with no side effects from ATT. Knee TB should be considered in patients from TB-endemic areas presenting with unexplained knee symptoms, particularly when there is a history of pulmonary TB. Early diagnosis through biopsy and appropriate imaging is essential for effective management. Comprehensive treatment, including ATT and surgical debridement, followed by rehabilitation, leads to favorable outcomes in most cases.